2008
DOI: 10.1158/1055-9965.epi-08-0605
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin as a Biomarker of Circadian Dysregulation

Abstract: It would be most useful to identify a biomarker of circadian dysregulation that could be used in epidemiologic studies of the effects of circadian disruption in humans. An indicator of circulating melatonin level has been shown to be a good biomarker of circadian dysregulation and has been associated with nightshift work and exposure to light-at-night in both laboratorybased and field studies. Among other circadian markers (such as core body temperature), it remains comparatively robust in the presence of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(118 citation statements)
references
References 120 publications
2
108
0
2
Order By: Relevance
“…40 Our findings might suggest the potential use of exogenous melatonin treatment of patients with AD to improve sleep efficiency and skin inflammation.…”
Section: Figurementioning
confidence: 74%
“…40 Our findings might suggest the potential use of exogenous melatonin treatment of patients with AD to improve sleep efficiency and skin inflammation.…”
Section: Figurementioning
confidence: 74%
“…In contrast to our results, Borisenkov et al [6] reported circadian variations in salivary TAC concentrations with maximum at 6.00 a.m. and minimum at 3 p.m. and suggested that the influence of melatonin in the morning increases TAC. Melatonin, an important circadian marker which synchronizes the internal hormonal environment according to the light-dark cycle, has been proved to be an effective antioxidant [31,44]. Melatonin is measurable in saliva and significant correlation was reported between melatonin concentrations in blood and saliva [35].…”
Section: Effect Of Circadian Rhythmmentioning
confidence: 99%
“…MLT is a leading candidate for mediating the putative ALANinduced circadian disruption at the molecular, hormonal, and epigenetic levels. Therefore, MLT serves as an operational biomarker for circadian disruption and a promising chronobiotic drug target for circadian disruption-related diseases [245]. Enhancement of the circadian amplitude by pharmalogical agents, such as Nobiletin, has been found to ameliorate circadian disruption-related syndromes, such as obesity and metabolic disorders [246].…”
Section: Discussionmentioning
confidence: 99%